2017
DOI: 10.1021/acs.analchem.7b01723
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Ultrafine Au–Ag Alloy Nanoparticles Used for Colorimetric Chiral Recognition and Circular Dichroism Sensing of Enantiomers

Abstract: Despite a significant surge in the number of investigations into chirality at the nanoscale, especially thiolated chiral molecules capping gold clusters, only limited knowledge is currently available to elaborate the alloying effect on chiroptical behavior of bimetallic nanoparticles (NPs). Also, few successful cases as to the efforts toward the development of chirality-dependent applications on the optically active nanomaterial have been made. Herein, as a positive test case for chiral alloy nanoparticle synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 48 publications
(85 reference statements)
1
39
0
Order By: Relevance
“…Chiral AgNCs that possess both CD and circularly polarized luminescence (CPL) signatures were reported recently, where the chirality in ligand staples likely gave rise to the chiroptical activity in the emission states[191]. Chirality is also observed in alloying (doping) UNMNPs such as Au-Pd[192–194] and Au-Ag[195197] nanoparticles. Understanding the fundamentals of chirality in these ultrasmall nanosystems is indispensable for the advancement of future applications.…”
Section: Breakthrough In Understanding the Physical Properties Of Unmnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral AgNCs that possess both CD and circularly polarized luminescence (CPL) signatures were reported recently, where the chirality in ligand staples likely gave rise to the chiroptical activity in the emission states[191]. Chirality is also observed in alloying (doping) UNMNPs such as Au-Pd[192–194] and Au-Ag[195197] nanoparticles. Understanding the fundamentals of chirality in these ultrasmall nanosystems is indispensable for the advancement of future applications.…”
Section: Breakthrough In Understanding the Physical Properties Of Unmnpsmentioning
confidence: 99%
“…Chirality serves as an important aspect of specific molecular recognition within biosystem and is crucial for areas such as pharmaceuticals and agrochemicals. UNMNPs-based biomolecule chiral recognition and enantiomer sensing were demonstrated recently, through either the individual nanoparticles[197] or their three-dimensional assembly[214].…”
Section: Breakthrough In Understanding the Physical Properties Of Unmnpsmentioning
confidence: 99%
“…Bimetallic nanoparticles (NPs) attract significant attention because they usually exhibit more interesting catalytic, [1][2][3] photocatalytic, [4] electrocatalytic, [5,6] and optical properties [7,8] than do their corresponding monometallic NPs. We previously reported that the simple physical mixture of different NP sols spontaneously leads to the formation of core/shell structured bimetallic NPs (Scheme 1) [9][10][11][12] or an ano-alloy, [13] and am ixture of palladium NPs and gold ions forms crown-jewel typeb imetallic NPs.…”
mentioning
confidence: 99%
“…Various methods have been used for the chiral recognition of enantiomers, in particular, optical methods, such as colorimetry [4,5,6,7], spectrofluorimetry [8,9,10,11] and circular dichroism (CD) spectroscopy [12,13,14,15,16,17,18] have received great interest due to their apparent advantages over other methods by virtue of their high sensitivity and the convenience in operation. CD spectroscopy is generally utilized to analyze the molecular chirality, which is sensitive to the conformational changes of the chiral molecules.…”
Section: Introductionmentioning
confidence: 99%